2017
DOI: 10.1590/1980-5373-mr-2016-0569
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Surface Oxygen-deficient BiPO4 Nanocubes with Enhanced Visible Light Induced Photocatalytic Activity

Abstract: The visible light driven BiPO 4 nanocubes with sufficient surface oxygen deficiency were fabricated by a hydrothermal process and subsequently ultrasonic assistant Fe reduction process. The products were characterized by XRD, DRS, XPS, SEM and TEM which showed that the BiPO 4 had cuboid-like shape with a smooth surface and clear edges and the oxygen vacancies were succesfully introduced on the surface of the BiPO 4 nanocubes. The as prepared oxygen-deficient BiPO 4 nanocubes showed greatly enhanced visible lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[23][24][25] However, the ultraviolet light only accounts for a small portion of sunlight, which limits the application of BiPO 4 in photocatalytic degradation. [26][27][28] As an outstanding up-conversion luminescence agent, Er 3+ :Yb n Y 3−n Al 5 N x F y O 12−x−y has a broad development prospect because it can make full use of low energy lights and provide high energy ultraviolet light. Therefore, the use of Er 3+ :Yb n Y 3−n Al 5 N x F y O 12−x−y can be used for satisfying the requirement of BiPO 4 for ultraviolet light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] However, the ultraviolet light only accounts for a small portion of sunlight, which limits the application of BiPO 4 in photocatalytic degradation. [26][27][28] As an outstanding up-conversion luminescence agent, Er 3+ :Yb n Y 3−n Al 5 N x F y O 12−x−y has a broad development prospect because it can make full use of low energy lights and provide high energy ultraviolet light. Therefore, the use of Er 3+ :Yb n Y 3−n Al 5 N x F y O 12−x−y can be used for satisfying the requirement of BiPO 4 for ultraviolet light.…”
Section: Methodsmentioning
confidence: 99%
“…No references were found on modeling of the PIP process for CMCs, though experimental studies on this manufacturing process have been reported. Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
mentioning
confidence: 99%
“…Photocatalysis demonstrates superior advantages over other techniques. They include ecological friendliness, capability of performance at ambient temperatures and efficiency to effectively degrade pollutants even at low concentrations [ 150 ]. The principal aim of photocatalysis is centered on the development of efficient photocatalysts that effectively utilize sunlight [ 151 ].…”
Section: Energy Applications Inspired By Butterfly Wingsmentioning
confidence: 99%
“…At the same time, creative and yet-to-be-devised approaches to fix its drawbacks are needed to benefit from this promising photocatalyst for its use in photocatalytic wastewater treatment. Several approaches have been already reported to enhance the adsorption ability and visible light response of BiPO4 such as doping [20][21][22], heterojunction systems [23][24][25], oxygen vacancy [26][27][28][29], phase junction [30][31][32], and combination with π-conjugated materials [33][34][35].…”
Section: Introductionmentioning
confidence: 99%